2017
DOI: 10.1016/j.jaci.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Group 2 innate lymphoid cells are recruited to the nasal mucosa in patients with aspirin-exacerbated respiratory disease

Abstract: Background Aspirin-exacerbated respiratory disease (AERD) is characterized by tissue eosinophilia and mast cell activation, including abundant production of prostaglandin D2 (PGD2). Group 2 innate lymphoid cells (ILC2s), which promote tissue eosinophilia and mast cell responses, undergo chemotaxis and cytokine production in response to PGD2 but it is unknown whether ILC2s are active in AERD. Objective We sought to determine whether ILC2 numbers change in peripheral blood and nasal mucosa during cyclooxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 39 publications
(64 reference statements)
4
61
1
Order By: Relevance
“…This is in line with the findings in asthmatic patients where after allergen challenge, D prostanoid receptor 2 (DP2 or CRTH2) positive ILC2s were significantly increased in sputum and correlated with airway eosinophilia . In addition, Eastman et al found that ILC2s were recruited to the nasal mucosa in patients with aspirin‐exacerbated respiratory disease. Using murine models, two recent researches confirmed the important role of ILC2s in exacerbating type 2 inflammation in AR …”
Section: Introductionsupporting
confidence: 84%
“…This is in line with the findings in asthmatic patients where after allergen challenge, D prostanoid receptor 2 (DP2 or CRTH2) positive ILC2s were significantly increased in sputum and correlated with airway eosinophilia . In addition, Eastman et al found that ILC2s were recruited to the nasal mucosa in patients with aspirin‐exacerbated respiratory disease. Using murine models, two recent researches confirmed the important role of ILC2s in exacerbating type 2 inflammation in AR …”
Section: Introductionsupporting
confidence: 84%
“…Cysteinyl leukotrienes have long been known to promote airway inflammation, AHR and airway remodeling (1, 2, 38). Recently, we reported increased ILC2s in the nasal mucosa of patients with aspirin exacerbated respiratory disease (AERD) which is characterized by increased CysLTs and PGD2, both of which could recruit and activate ILC2s (39). Further, roles for IL-33 and TSLP in AERD have also been identified, thus supportive of a mediator milieu related to our current studies (40, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Eastman et al . reported that ILC2 cells were specifically recruited to nasal mucosa in patients with aspirin‐exacerbated respiratory disease during aspirin challenge, with a paradoxical increase in urinary PGD 2 metabolite, 11β‐PGF 2 (Eastman et al ., ). This study indicates that PGD 2 may have critical roles in recruiting and activating ILC2s through DP 2 receptors in aspirin‐exacerbated respiratory disease.…”
Section: Pg‐cytokine Crosstalk In Immune and Allergic Inflammationmentioning
confidence: 97%